ICT literacy, resilience and online learning self-efficacy between Chinese rural and urban primary school students - Li, Jiaxin; Huang, Xinyi; Lei, Xinyu; Wen, Jiajie; Lu, Minghui (Frontiers in Psychology, 2022)
In the process of large-scale online education during the COVID-19 pandemic, students’ online learning has caused widespread public concerns. This study investigated the relationships between Chinese rural and urban primary school students’ information communications technology (ICT) literacy, student resilience, and online learning self-efficacy in a large-scale online education environment during the pandemic in China. We compared 5,037 primary school students in rural areas to 5,045 primary school students in urban areas with matching gender and grade in nine regions in China’s Guangdong province, using a survey comprising an ICT literacy scale, a student resilience scale, an online learning self-efficacy scale, and an ICT devices scale. The ICT literacy, resilience and online learning self-efficacy of primary school students in rural areas were significantly lower than those in urban areas (p < 0.01). The primary school students’ ICT literacy was significantly associated with student resilience and online learning self-efficacy. Student resilience played a mediating role between ICT literacy and online learning self-efficacy, while the rural/urban area factor moderated the relationship between ICT literacy and student resilience. These findings suggest that ICT literacy is more scarce and important for primary school students in rural areas of China than for those in urban areas. Improving ICT literacy among primary school students can enhance students’ resilience and thus improve their online learning self-efficacy, especially in rural areas.